Why Do Demand Curves for Stocks Slope Down? - Petajisto, Antti (Journal of Financial and Quantitative Analysis, 2009)
Abstract Representative agent models are inconsistent with existing empirical evidence for steep demand curves for individual stocks. This paper resolves the puzzle by proposing that stock prices are instead set by two separate classes of investors. While the market portfolio is still priced by individual investors based on their collective risk aversion, those individual investors also delegate part of their wealth to active money managers, who use that capital to price stocks in the cross section. In equilibrium, the fee charged by active managers has to equal the before-fee alpha they earn. This endogenously determines the amount of active capital and the slopes of demand curves. A calibration of the model reveals that demand curves can be steep enough to match the magnitude of many empirical findings, including the price effects for stocks entering or leaving the S&P 500 index.